Impacts of School Communication on Job Satisfaction in Australian Primary Schools: A Structural Equation Model - De Nobile, John; Bilgin, Ayse Aysin (Frontiers in Education, 2022)
While there has been research into the ways some aspects of organizational communication may influence job satisfaction, it has not been comprehensive, and very little work has been conducted in schools. This study investigates the influences of a comprehensive range of aspects of organizational communication on job satisfaction of school staff. Participants in the study were 1,575 staff members from schools across Australia. A questionnaire survey was the primary instrument. Data were analyzed using exploratory and confirmatory factor analyses to validate constructs and multiple regression analyses, followed by structural equation modeling, to investigate effects. A 10 factor model of aspects of organizational communication and six-factor model of job satisfaction dimensions were identified and validated. Multiple regression analyses revealed that all 10 aspects of organizational communication have associations with job satisfaction. However, structural equation modeling revealed five aspects of organizational communication, to do with openness, support-giving, principal direction, and participation in decision making to have the most important effects on job satisfaction. This study contributes to our knowledge of communication by confirming a 10-factor model of organizational communication that can be used in other research. Implications for practice include the need for school leadership to foster open communication and facilitate school climates that encourage supportiveness, democracy, and collegial direction.